1996
DOI: 10.1111/j.0953-0673.1996.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic interactions between omeprazole and amoxycillin in Helicobacter pylori‐positive healthy subjects.

Abstract: High-dose omeprazole does not alter the pharmacokinetics of amoxycillin. The significantly lower intragastric pH during combination therapy might be due to the H. pylori-suppressive effect of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Mainz reported that the pharmacokinetics of amoxicillin were not altered by combination therapy with lansoprazole and clarithromycin [8] , which is consistent with other reports that demonstrated no effects of omeprazole on the pharmacokinetics of amoxicillin [21][22][23] . Therefore, in present study, we did not compare the plasma concentration of amoxicillin alone with combination therapy because of its non-metabolic characteristics.…”
Section: Discussionsupporting
confidence: 85%
“…Mainz reported that the pharmacokinetics of amoxicillin were not altered by combination therapy with lansoprazole and clarithromycin [8] , which is consistent with other reports that demonstrated no effects of omeprazole on the pharmacokinetics of amoxicillin [21][22][23] . Therefore, in present study, we did not compare the plasma concentration of amoxicillin alone with combination therapy because of its non-metabolic characteristics.…”
Section: Discussionsupporting
confidence: 85%
“…The drug regimen should be based susceptibility testing using biopsies from the patient, stool specimens, or more commonly by knowledge of the success rates of different therapies in the local area and in one's practice. Other considerations include cost and availability of drugs and should take into account the difference in pharmacokinetics and pharmacodynamics of the drugs available [25][26][27][28][29] .…”
Section: Host Factors Influencing Treatment Successmentioning
confidence: 99%
“…Omeprazole was launched as the fi st PPI in the United States under license by Merck, Sharp & Dohme (West Point, Pennsylvania) in 1989 [ 2 ] . It has been playing an dominant role in clinical treatment of the acid-related disorder diseases and combined regimen against Helicobacter pylori compared with other PPIs during the past decade [ 3 ] . However, omeprazole is acid-labile and decomposes rather rapidly at pH < 5 [ 4 ] .…”
mentioning
confidence: 99%